The roles of newspapers ownership pattern and access to governmental information in framing of issues of corruption in Sudan - Hamid, Yassin Bashir; Mohammed, Rosli; Ahmad, Mohd Khairie (GSSRR, 2017)
Corruption is a global threat to state efficiency which is common to both developed and developing countries alike.However, corruption is more evident in developing countries such as; Sudan and its ravaging effects are particularly apparent in Sudan.However, the media contributes largely to the success of democracy in today’s world.They carry a large database of information, along with their content and analyses, which could be a useful source for law makers to legislate laws and policies and for voters to choose their governments.As such, this paper set out to address the issue of corruption in Sudan within the context of Sudanese press by focusing on how media ownership and access to information influence the Sudanese press frames the coverage of issues of corruption in Sudan.This study therefore proposes a content analysis of Sudanese newspaper on their coverage of the issues of corruption.As with every other research, the limitation of this study is that, it is a conceptual paper, hence no empirical findings have been reported.Therefore, an empirical study into this issue will help researchers to explore how far the press or media in Sudan are capable of addressing anti-corruption issues in the country.